Antidiabetic Effect of Fenugreek Seed Powder Solution (Trigonella foenum-graecum L.) on Hyperlipidemia in Diabetic Patients - Genet Alem Geberemeskel; Yared Godefa Debebe; Nigisty Abraha Nguse (Journal of Diabetes Research)
Background. Many drugs are commercially available for use in the management of diabetes. However, their side effects and high costs underscore the need for herbal alternative drugs. Trigonella foenum-graecum is one of the medicinal plants which are important in the management of diabetes mellitus. This study investigated the effect of Trigonella foenum-graecum seed powder solution on the lipid profile of newly diagnosed type II diabetic patients. Methods. A total of N=114 newly diagnosed type II diabetic patients without any significant diabetes complication were selected. They were grouped into two groups: the treatment group (n=57) consumed 25 g Trigonella foenum-graecum seed powder solution orally twice a day for one month and the second group is the control (n=57) which receives metformin. Blood sample was collected from each participant by a medical technologist/technician before and after the study. Lipid profile was analyzed by using Mindray BS 200E fully automated clinical chemistry analyzer. Result. By the end of the intervention period, the treatment group showed significantly lower total cholesterol level by 13.6% as compared with the baseline level (219.1±35.51 vs. 189.29±29.06, P<0.001) and the control group (189.29±29.06 vs. 208.2±40.2, P<0.001); triglyceride level also reduced by 23.53% compared with the baseline level (256.1±15.4 vs. 195.8±82.95, P<0.001) and compared with the control group (195.8±82.95 vs. 244.1±96.9, P<0.05); and low-density lipoprotein cholesterol level also reduced by 23.4% as compared to the baseline level (137.9±26.9 vs. 105.6±24.2, P<0.001) and the control group (between groups) (105.6±24.2 vs. 144.1±23.3, P<0.001), but the treatment group showed significantly increased high-density lipoprotein cholesterol level by 21.7% as compared to the baseline level, within group (37.8±1.51 vs. 48.3±11.9, P<0.001), and the control group, between groups (48.3±11.9 vs. 36.01±9.5, P<0.001). However, lipid profile levels in the control group were not significantly changed. Conclusion. The present study showed that the administration of Trigonella foenum-graecum seed powder solution had pronounced effects in improving lipid metabolism in type II diabetic patients with no adverse effects. Therefore, Trigonella foenum-graecum seed may provide new alternatives for the clinical management of type II diabetes.